1998
DOI: 10.1016/s0928-8244(98)00011-x
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages recognize and adhere to an OmpD-like protein of Salmonella typhimurium

Abstract: Murine peritoneal macrophages bind to Salmonella typhimurium in vitro in the absence of exogenous opsonins. We have identified an outer membrane protein of S. typhimurium that mediates this adhesion. Biotin-labeled macrophages were used to probe electroblotted envelope proteins of S. typhimurium that had been previously resolved by polyacrylamide electrophoresis under denaturing and reducing conditions. Macrophages bound to an outer membrane protein with an apparent molecular mass of 44 kDa. The protein was pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
0
9
2
Order By: Relevance
“…In contrast, earlier studies from our laboratory showed a 5-fold decrease in attachment of an ompC mutant to murine peritoneal macrophages compared with the wild-type strain (Negm and Pistole 1999). Our laboratory also showed that picomolar concentrations of an OmpD-like protein from Salmonella serovar Typhimurium inhibited attachment of this microorganism to murine peritoneal macrophages (Negm and Pistole 1998).…”
Section: Introductioncontrasting
confidence: 88%
See 1 more Smart Citation
“…In contrast, earlier studies from our laboratory showed a 5-fold decrease in attachment of an ompC mutant to murine peritoneal macrophages compared with the wild-type strain (Negm and Pistole 1999). Our laboratory also showed that picomolar concentrations of an OmpD-like protein from Salmonella serovar Typhimurium inhibited attachment of this microorganism to murine peritoneal macrophages (Negm and Pistole 1998).…”
Section: Introductioncontrasting
confidence: 88%
“…There was no significant difference in binding for the 2 strains (p = 0.704, n = 4). murine peritoneal macrophages (Negm and Pistole 1998). They differ, however, from those of Meyer et al (1998), who found no significant difference in adherence of wild-type and ompD mutant Salmonella serovar Typhimurium to 407 cells, a human intestinal cell line.…”
Section: Discussioncontrasting
confidence: 68%
“…In S . Typhimurium, OmpC and OmpF porins are recognized by macrophages, participate in phagocytosis and trigger a signaling cascade which regulates the ROS response by the host and the phagolysosomal maturation [13], [14]. Furthermore, mutants in the S .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that OmpD is involved in adherence and recognition of S . Typhimurium to human macrophages and intestinal epithelial cells, during the initial stages of infection [13], [20]. Moreover, studies based on the B1b cell antibody response showed that OmpD is a key factor in the humoral response in mice [21].…”
Section: Introductionmentioning
confidence: 99%
“…The OmpD porin must play a critical role in the survival of S. typhimurium in certain environments, because OmpD facilitates the entry of some critical nutrients (Nikaido, 1996). Furthermore, OmpD may also play a critical role in the interactions between S. typhimurium and host cells, and is likely to be involved in the adhesion of S. typhimurium to murine macrophages (Negm & Pistole, 1998). The characterization of this important genomic difference between S. typhi and other Salmonella serovars that includes ompD is significant for the following three reasons.…”
Section: Discussionmentioning
confidence: 99%